Teknik Relaksasi Nafas Dalam untuk Meringankan Nyeri Dismenore pada Remaja Putri di Bergas Lor - Dania Aprilia; Cahyaningrum; putri cahya (Universitas Ngudi Waluyo, 2022)
Adolescence is a period of dynamic development in one's life and is a period of transition from childhood to adulthood. During this period many physical, psychological and biological changes occur. This is the period where the maturation of the reproductive organs occurs, one of which in young women is marked by menstruation (menstruation). Menstruation also often causes pain which is called dysmenorrhea. Dysmenorrhea is discomfort during the first or second day of menstruation which is very common. Deep breathing relaxation technique is a theory from Huges which is effective in reducing pain intensity. Deep breathing technique is one of the conditions that can stimulate the body to release endogenous opoids so that a suppression system is formed which will eventually lead to a decrease in pain intensity.The steps taken in carrying out a complementary midwifery service program regarding deep breathing relaxation techniques to relieve dysmenorrhea pain, namely by determining the right target. The target criteria for this community service activity are teenagers who want to relieve dysmenorrhea. The steps taken in carrying out deep breathing relaxation techniques, namely by determining the right target, then doing a pre test, counseling, demonstration, then a post test. The target criteria for this community service activity are young women at Bergas Lor. Based on all the stages that have been carried out, it can be seen that the majority of young women (78%) do not know deep breathing relaxation techniques. After counseling and demonstrations, all young women (100%) already understand and can apply this technique well. This deep breathing relaxation technique has been proven in overcoming dysmenorrhea experienced by young women at Bergas Lor. This result is in line with the statement of Brahim, et al (2020), which states that deep breathing relaxation techniques performed for 15-30 minutes can relax the body and generally provide a sense of comfort, so that the intensity of pain felt gradually disappears. Abstrak Masa remaja merupakan masa fase perkembangan dinamis dalam kehidupan seseorang dan merupakan periode transisi dari masa anak-anak ke masa dewasa. Pada masa ini banyak terjadi perubahan fisik, psikis, dan biologis. Masa inilah terjadi pematangan organ reproduksi, salah satunya pada remaja putri ditandai dengan menstruasi (haid). Menstruasi juga sering menyebabkan nyeri yang disebut dismenore. Dismenore adalah ketidaknyamanan selama hari pertama atau hari kedua menstruasi yang sangat umum terjadi. Teknik relaksasi nafas dalam merupakan teori dari Huges yang efektif dalam menurunkan intensitas nyeri. Teknik nafas dalam merupakan salah satu keadaan yang mampu merangsang tubuh untuk mengeluarkan opoid endogen sehingga terbentuk sistem penekanan yang akhirnya akan menyebabkan penurunan intensitas nyeri. Langkah-langkah yang dilakukan dalam melakukan teknik relaksasi nafas dalam, yaitu dengan menentukan sasaran yang tepat, lalu melakukan pre test, penyuluhan, demostrasi, kemudian post test. Kriteria sasaran dalam kegiatan pengabdian masyarakat ini adalah remaja putri di Bergas Lor. Berdasarkan keseluruhan tahapan yang telah dilakukan, dapat diketahui bahwa mayoritas remaja putri (78%) tidak mengetahui teknik relaksasi nafas dalam. Setelah dilakukan penyuluhan dan demostrasi, remaja putri semuanya (100%) sudah mengerti dan dapat menerapkan teknik ini dengan baik. Teknik relaksasi nafas dalam ini terbukti dalam mengatasi dismenore yang dialami para remaja putri di Bergas Lor. Hasil ini sejalan dengan pernyataan Brahim, dkk (2020), yang menyatakan bahwa teknik relaksasi nafas dalam yang dilakukan 15-30 menit dapat merelaksasikan tubuh dan secara umum memberikan rasa nyaman, sehingga intensitas nyeri yang dirasakan berangsur menghilang.